2020
DOI: 10.1111/bcp.14404
|View full text |Cite
|
Sign up to set email alerts
|

Warfarin and food, herbal or dietary supplement interactions: A systematic review

Abstract: Aims To present an updated overview on the safety of concurrent use of food, herbal or dietary supplement and warfarin. Methods A systematic literature review was performed on 5 databases from inception up to 31 December 2019. These interactions were classified depending on the likelihood of interaction and supporting evidences. Results A total of 149 articles describing 78 herbs, food or dietary supplements were reported to interact with warfarin. These reports described potentiation with 45 (57.7%) herbs, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(47 citation statements)
references
References 161 publications
(257 reference statements)
0
43
0
4
Order By: Relevance
“…Warfarin interacts with various drugs and foods and inhibits vitamin K-dependent coagulation factors. It is metabolized by cytochrome P450 (CYP450) isozymes; furthermore, it has a high protein-binding rate [6][7][8][9]. BM is immediately hydrolyzed to its active form, S-033447 [1], which has a high protein-binding rate (93%-94%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Warfarin interacts with various drugs and foods and inhibits vitamin K-dependent coagulation factors. It is metabolized by cytochrome P450 (CYP450) isozymes; furthermore, it has a high protein-binding rate [6][7][8][9]. BM is immediately hydrolyzed to its active form, S-033447 [1], which has a high protein-binding rate (93%-94%).…”
Section: Discussionmentioning
confidence: 99%
“…Their prothrombin time-international normalized ratio (PT-INR), an indicator of warfarin efficacy, is precisely controlled [5]. Warfarin poses a clinical problem because the PT-INR fluctuates due to the drug's interactions with other drugs and vitamin K intake [6][7][8][9]. Here, we report a case of a patient with iVAD whose PT-INR was significantly increased from the target range with the intake of BM.…”
Section: Introductionmentioning
confidence: 99%
“…This study showed T&CM was commonly used among patients with type 2 diabetes in multi-ethnic communities (see Figure 1). Of clinical concern, these patients have a high risk of adverse drug events, principally those of older age and have multiple chronic medical conditions [12] . The risk is further increased in light of the challenges to determine specific ingredients in T&CM products, no tablet size and shape requirements, and lack of postmarketing surveillance [13] .…”
Section: Discussionmentioning
confidence: 99%
“…Ginger exerts antiplatelet actions in preclinical experiments and thus might theoretically interact with antiplatelet and/or anticoagulant drugs (Izzo, 2012). A recent systematic review of the literature retrieved three cases of interaction between ginger, the anticoagulant warfarin (Tan & Lee, 2020). However, a clinical trial showed that consumption of ginger, at recommended doses, does not significantly affect the pharmacokinetics or pharmacodynamics of warfarin in healthy subjects (Jiang et al, 2005).…”
Section: Safetymentioning
confidence: 99%